MEDIA SOSIAL DALAM MEMBENTUK POLA KOMUNIKASI DAN PEMIKIRAN GENERASI Z: TINJAUAN EMPIRIS TIGA TAHUN TERAKHIR - Fitriana, Fitriana (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2024)
This research explores the influence of social media on the communication patterns and thinking structures of Generation Z, the first generation to grow up in a digital environment. Using a descriptive qualitative method with a literature study approach, this research collected data from various sources to understand the impact of social media. The results show that Generation Z tends to use visual-based and ephemeral communication, which results in a decline in critical thinking and deep information processing, and creates social pressure that impacts their mental health. In addition, while social media provides opportunities for self-expression and social connection, challenges such as stress and difficulty in understanding complex issues also arise. In conclusion, it is important for Generation Z to develop digital literacy and critical thinking skills in order to utilize social media wisely, so this study is expected to provide insights for designing relevant interventions in education and psychology to support their well-being in the digital age.